Phylogenetic analysis blaTEM gene of Escherichia coli isolated from cave bats in West Nusa Tenggara Province, Indonesia - Alfiana Laili Dwi Agustin; Mustofa Helmi Effendi; Wiwiek Tyasningsih; Hani Plumeriastuti; Aswin Rafif Khairullah; Fitrine Ekawasti; Ikechukwu Benjamin Moses; Kurnia Nisa Kinasih; Muhammad Khaliim Jati Kusala; Yolla Rona Mustika; Ima Fauziah; Syahputra Wibowo (Open Veterinary Journal)
Background: The blaTEM, blaCTX-M and blaSHV are the result of mutations in the ESBL enzyme which can be seen genotypically. Wild bats have never received antibiotic therapy, the presence of AMR in bats indicates the level of AMR in the environment, the circulation of ESBL Escherichia coli between humans or animals in Indonesia and wild animals is still not widely known. Whole genome sequencing is used to determine the circulation of ESBL Escherichia coli in detail.